The Effects of Using Gadgets during the Covid-19 Pandemic on Children's Behaviour - Ilga Maria; Ria Novianti (Institut Agama Islam Negeri Langsa, 2020)
During the Covid-19 pandemic, school from home (SFH) policy was regulated with the aim of inhibiting the spread of the virus. The SFH process makes children interact frequently with gadgets because learning is occurred online, however in practice, they must refer to the national curriculum. This study aims to find out the effects of using gadgets during the Covid-19 pandemic on children's behavior. This research is a descriptive quantitative research. The population of the study were 74 kindergarten’ students in Pekanbaru City, Riau Province. Researchers took 50% of the population so that from 74 people, 30 children were taken to be the trial sample and the rest were the research samples, as many as 37 children. The results showed that the most dominant effect of using gadgets during the Covid-19 pandemic on children's behavior was in the compulsion indicator. For further research, it can be investigated the influence of these aspects with parenting styles.